Anti-inflammatory, antimicrobial and antioxidant activity of propolis and geopropolis produced by stingless bees - Ripari, Nicolas [UNESP]; Sforcin, José Maurício [UNESP] (Springer Nature, 2024)
Stingless bees live in colonies ranging from hundreds to many thousands of individuals, but studies are scarce regarding resin, like the propolis of Apis mellifera. Several biological activities of propolis and geopropolis produced by meliponines have been described and, in this chapter, we focus on anti-inflammatory, antimicrobial, and antioxidant activities. Understanding the chemical profile of geopropolis and propolis, and the diverse pathways involved in their anti-inflammatory, antimicrobial, and antioxidant effects, is challenging. These bee products have been mainly extracted in ethanolic solvents and their anti-inflammatory action is related to immunomodulatory and antioxidant effects. Their compounds have low toxicity in vitro and in vivo for normal cells but display an antimicrobial activity. Geopropolis and propolis compounds may act synergistically to produce immunomodulators and antimicrobials.
Keywords: Anti-inflammatory activity; Antimicrobial activity; Antioxidant activity; Geopropolis; Stingless bees propolis